Chikungunya-an outbreak investigation report from Nagpur, Maharashtra 2024 - Gandhare, Pratiksha M.; Khadse, Ravindra R.; Babhulkar, Asmita V. (International Journal Of Community Medicine And Public Health, 2025)
Background: Chikungunya is important re-emerging viral threat in developing and developed countries. It is characterized by high fever, headache, skin rash, incapacitating arthralgia, prominent polyarthralgia, and myalgia that can last weeks to months even years in some individuals resulting in negative social and economic impact. After 2006 epidemic, infection was in quiescent state and there were sporadic cases in Vidharbha region of Maharashtra. Chikungunya outbreak has currently affected Mangalwari zone no.10 and neighboring areas. Methods: After surveying the affected area of Nagpur, four types of investigations were done for data collection like epidemiological, clinical, entomological and behaviour related investigation. Serum samples were collected from suspected cases and subjected to chikungunya IgM MAC capture ELISA. Results: A total of 130 suspects were tested for chikungunya IgM ELISA, of which 54 samples were positive. The attack rate was calculated as 41.53%. Outbreak occurred in hot months of June. Fever survey and entomological survey has revealed that situation was under control due to strict government actions but cases increased as monsoon arrived. High larval indices revealed that there is high Aedes mosquito density and further risk of outbreaks. Conclusions: Public awareness and community participation for mosquito population control is crucial for prevention of further outbreaks.